Projects of degree in the faculty of education - Fanny Morales Valenzuela (Corporación Universitaria Minuto de Dios, 2004)
The education faculty following the institutional vision promoted in the students who were doing their projects to obtain the academic title the need to participate in real situations with marginal and unprotected communities. Talking in this way a social and academic compromise. The works to obtain the academic title present pedagogic experiences in close relation with the emphasis. These works try to understand realities in which practice and theory are together. Form this practice many academic meetings were done besides many researching lines were created.